Analisis Korelasi Overbreak Terhadap Yield Zone Pada Area 601 Crusher Complex Tambang Bawah Tanah Grasberg Block Cave PT. Freeport Indonesia - Zet Rahmadanil; Bambang Heriyadi (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract. PT. Freeport Indonesia uses two mining systems, namely open pit and underground mining. Underground mining generally uses the block caving method. One of the facilities built on the GBC underground mine is Crusher. The crushers used in the GBC underground mine area are Gyratory type crushers. This crusher is located at location 601 at the level of 2760-2700 masl. Based on the results of observations in the field, it was found that the frequent occurrence of differences in tunnel size between the design and actual field 601 complex crusher is a fix facility opened by blasting. In addition, over break causes a change in the depth of the zone that must be supported, so that an equation is needed which can be used to determine the depth of the zone that must be supported. In the correlation analysis, the highest overbreak was 24.84%. The resulting effect is that the overbreak increases, the yield zone also increases in depth, from the initial design 2,073 meters to 3,127 meters after overbreak. The equation obtained from the overbreak correlation and yield zone is Y = 9,6727X2 – 6,751X + 21,129. Where Y is the maximum overbreak percent value that can be secured by a buffer. Recommendation equation Y = 9,6727X2 – 6,751X + 21,129 as a new parameter in the geotech department to provide buffer recommendations. Keywords: Overbreak, Yield Zone, Geotechnical, Correlation, Underground Mining